The role of the informal economy in achieving the sustainable development goals in Europe - Roberto Dell' Anno; Adriana Ana Maria Davidescu; Eduard Mihai Manta (Amfiteatru Economic, 2024)
This study investigated the relationship between the informal economy and sustainable development, focussing on how the shadow economy influenced the achievement of the 17 Sustainable Development Goals (SDGs) formulated in the 2030 Agenda in Europe. The research used data extracted from the Eurostat and Schneider (2022) and analysed sustainable development performance in 36 European countries in the years 2010 and 2022. The methodology involved applying partial least squares (PLS) regression to construct a synthetic indicator of sustainable development, considering two scenarios: one that excluded and another that included the size of the informal economy. The results highlighted that while the informal economy contributed to immediate poverty alleviation and short-term economic resilience, it created challenges for long-term sustainability in areas such as formal employment, social inclusion, and environmental regulation. The findings highlighted the need for stronger policies to integrate the informal sector into the formal framework, thus improving overall sustainability. The study made an original contribution by addressing the dual role of the informal economy in sustainable development, offering new perspectives for formulating more effective policies in the context of the 2030 Agenda.
Keywords: C51; E26; O17; Q01; Q56; 330; sustainable development; SDG; informal economy; composite indicators; PLS